2003
DOI: 10.1046/j.1470-6431.2003.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing online and non‐online shoppers

Abstract: A web‐based survey was completed by 130 faculty and staff from a university located in the south‐eastern United States. The purposes of this study were to investigate: (a) consumer characteristics related to online shopping; (b) benefits of online shopping as perceived by online shoppers; and (c) concerns about online shopping as perceived by non‐online shoppers. Responses were analysed using SPSS for tests of chi‐square. Findings suggest that the differences between online shoppers and non‐online shoppers cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 9 publications
(12 reference statements)
4
27
0
Order By: Relevance
“…Similar results were found in the paper that belongs to Hui and Wan (2006). According to Lokken et al (2003), there are persistent concerns about the security of online shopping which is valid for the "suspicious shoppers" segment found here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were found in the paper that belongs to Hui and Wan (2006). According to Lokken et al (2003), there are persistent concerns about the security of online shopping which is valid for the "suspicious shoppers" segment found here.…”
Section: Discussionsupporting
confidence: 89%
“…The relevant literature includes studies which investigate the factors affecting online shopping (LIMAYEM et al, 2000), compare online and non-online shoppers (Lokken et al 2003), examine the shopping and buying behavior of younger and older online shoppers (Sorce et al, 2005) and identify the role of gender and educational level on the attitudes of Internet users (Hui and Wan, 2006). There are also papers which aim to profile internet buyers in different countries (Lynch and Beck, 2001) and to model how socio-demographic variables, attitudes and beliefs towards internet shopping affect both the adoption decision and usage of the online shopping channel (Soopramanien and Robertson, 2007).…”
Section: Segmentation Of Online Shoppersmentioning
confidence: 99%
“…Apparently, this approach did sample participants with higher level of education than average population. That is in line with the findings by prior studies (Lokken et al, 2003;Nathan & Yeow, 2011), which found that online shoppers were more well-educated and technology savvy than average population.…”
Section: Empirical Data Collection -Participants and Proceduressupporting
confidence: 93%
“…43 By far most of the popular products offered online have been discretionary items (for example, travel, holidays and entertainment) which are suitable for affl uent consumers with higher disposable incomes. 55 Higher income is also associated with access to faster internet which, in turn, has shown to facilitate online shopping decisions. 43,54 Meanwhile, the online literature has linked fi nancial risk to adoption behaviour as well.…”
Section: 47mentioning
confidence: 99%